2007
DOI: 10.1097/pas.0b013e31806bee6d
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Nondysplastic and Dysplastic Serrated Polyps of the Vermiform Appendix

Abstract: Serrated colorectal polyps often show DNA hypermethylation and/or BRAF mutations and have been implicated in the "serrated neoplastic pathway." Although similar lesions occur in the appendix, they have never been systematically investigated. We evaluated a study group of 56 serrated polyps, a control group of 17 mucinous cystadenomas, and 4 adenocarcinomas with adjacent serrated polyps of the appendix to better understand their pathogenesis. The study cases were classified as nondysplastic or dysplastic serrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 21 publications
4
45
1
1
Order By: Relevance
“…For each case, nonlesional tissue was manually removed from the tissue slides using surgical blades for each section examined and DNA was extracted from the remaining lesional tissue using the QIAamp DNA MiniKit (Qiagen Sciences, Valencia, CA). Polymerase chain reaction amplifications were performed using the following primers, as previously described 43 :…”
Section: Molecular Methodsmentioning
confidence: 99%
“…For each case, nonlesional tissue was manually removed from the tissue slides using surgical blades for each section examined and DNA was extracted from the remaining lesional tissue using the QIAamp DNA MiniKit (Qiagen Sciences, Valencia, CA). Polymerase chain reaction amplifications were performed using the following primers, as previously described 43 :…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Most previous studies have identified KRAS mutation in a high proportion of disseminated low-grade mucinous neoplasms. 4,29 The frequent presence of activating KRAS mutations in disseminated mucinous neoplasms arising from the appendix is not surprising given that KRAS mutations have been identified in between 41 and 100% appendiceal mucinous adenomas 4,29,30 which are the presumed precursor lesion to disseminated neoplasms. Notably, none of the high-grade mucinous adenocarcinomas with signet ring cells (grade G3) composed of a pure (495%) signet ring cell component harbored a KRAS mutation suggesting that the underlying genetic events leading to carcinogenesis are different for grade G3 adenocarcinomas.…”
Section: Molecular Comparison Of Disseminated Appendiceal Mucinous Nementioning
confidence: 99%
“…Overexpression of p53 is reported to be rare in appendiceal tumors [4,6], although KRAS mutation and p53 overexpression can be seen in half of pseudomyxoma peritonei (PMP) cases of appendiceal origin [7]. Furthermore, microsatellite instability is rare in appendiceal carcinoma, and hypermethylation is not a mechanism for genetic instability in these tumors [8] although some hyperplastic polyps and sessile serrated adenomas of the appendix show decreased expression of MLH1 and BRAF mutation is more common in serrated polyps [9]. The Wnt signaling pathway that involves ␤-catenin plays a critical role in colorectal carcinogenesis, and approximately 90% of cases of colorectal carcinoma express nuclear ␤-catenin.…”
Section: Introductionmentioning
confidence: 98%